Analyses Based on Theory of Capital Based Approach on Indonesian Graduate Employability - Anak Agung Ayu Redi Pudyanti; A.A. Ngurah Agung Redioka; Viola Tashya Devana (ADI Publisher, 2022)
The employability of graduates is of global concern. This is one of the most important difficulties in ensuring a smooth transition of graduates from education to industry. Therefore, there are ongoing discussions in many countries about how to improve graduate employment. So the term